Development of Maritime Insight Learning Tools for Ocean Literacy in Children Aged 5-6 Years Old - Sahriana, Nanang; Suminar, Tri; Sugiyo Pranoto, Yuli Kurniawati (Universitas Negeri Semarang, 2020)
Indonesia as an archipelagic country should be introduced to early childhood. Therefore, it is necessary to develop maritime insight learning tools for children in coastal areas. The objectives of this research were to develop maritime insight learning tools for ocean literacy in children aged 5-6 years old and to analyze the effectiveness of the learning tools. The learning tools were in the form of semester program, weekly and daily lesson plan, teaching materials, and learning media and were developed by following the conditions and characteristics of the coastal areas. Research & Development with one group pretest-posttest design were conducted in six kindergartens with 80 students at Konawe Utara Regency, Southeast Sulawesi. The research also involved education experts, practitioners, and teachers of that areas as research subjects. Data collection instruments used were observation sheets, questionnaires, tests, and documentation. The results showed that the maritime insight learning tools is valid for use. The result of trials with t-test showed there were an increase in the ocean literacy skills of students after using maritime insight learning tools with n-Gain scores of 0.69 with the category medium on a limited scale trial and 0.70 with the high category in wide scale trial. It concluded that development of the maritime insight learning tools was effective for improving ocean literacy in children aged 5-6 years old